Hot stuff in the bushes: Thermal imagers and the detection of burrows in vegetated sites. Issue 11 (1st April 2021) - Cox, Tarnya E.; Matthews, Robert; Halverson, Grant; Morris, Stephen
Abstract: Thermal imaging technology is a developing field in wildlife management. Most thermal imaging work in wildlife science has been limited to larger ungulates and surface‐dwelling mammals. Little work has been undertaken on the use of thermal imagers to detect fossorial animals and/or their burrows. Survey methods such as white‐light spotlighting can fail to detect the presence of burrows (and therefore the animals within), particularly in areas where vegetation obscures burrows. Thermal imagers offer an opportunity to detect the radiant heat from these burrows, and therefore the presence of the animal, particularly in vegetated areas. Thermal imaging technology has become increasingly available through the provision of smaller, more cost‐effective units. Their integration with drone technology provides opportunities for researchers and land managers to utilize this technology in their research/management practices. We investigated the ability of both consumer (<AUD20, 000) and professional imagers (>AUD65, 000) mounted on drones to detect rabbit burrows (warrens) and entrances in the landscape as compared to visual assessment. Thermal imagery and visual inspection detected active rabbit warrens when vegetation was scarce. The presence of vegetation was a significant factor in detecting entrances ( p < .001, α = 0.05). The consumer imager did not detect as many warren entrances as either the professional imager or visual inspection ( p = .009, α = 0.05). Active warren entrances obscured by vegetation could not be accurately identified on exported imagery from the consumer imager and several false‐positive detections occurred when reviewing this footage. We suggest that the exportable frame rate (Hz) was the key factor in image quality and subsequent false‐positive detections. This feature should be considered when selecting imagers and suggest that a minimum export rate of 30 Hz is required. Thermal imagers are a useful additional tool to aid in identification of entrances for active warrens and professional imagers detected more warrens and entrances than either consumer imagers or visual inspection. Abstract : Thermal imaging technology is a developing field in wildlife management. We investigated the ability of both consumer and professional imagers mounted on drones to detect rabbit burrows (warrens) and entrances in the landscape as compared to visual assessment. Exportable frame rate (Hz) was the key factor in image quality and subsequent false‐positive detections. Thermal imaging technology provides an efficient method for detecting rabbit warrens and entrances in all vegetation types (open, vegetated, and mixed), surpassing visual inspection alone.